Analysis of a Lecturer’s Directive Speech Acts to Student in Online Pragmatic Studies - Gusti Ketut Alit Suputra; Idris Idris; Ali Ali; Astriana Astriana (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This research aims to describe the form and function of the lecturer's directive speech actions to Class A students in the 2019 batch participating in online learning in pragmatic studies. This research employed descriptive qualitative methods of observable words said by speakers (lecturers) to speech partners (students). The data source was the lecturer's remarks to students during online learning via zoom). The data collection techniques employed listening, note-taking, screen recording, and screenshots. The researcher discovered six types of directive speech acts including (1) a request form; (2) in the form of a lecturer's command; (3) A question; (4) a sort of prohibition; (5) An invitation in the style of Lecturer; and (6) As a demand.. Four directive speech acts functions are  (1) competitive (competing) functions; (2) convivial (fun); 3) collaborative function (collaborating); and (4) conflict function (contrary) as the lecturer said: If no one answers who wants to present their work, I will remove them from the zoom room”.